Contact and SARS-CoV-2 infections among college football athletes in the Southeastern Conference during the COVID-19 pandemic - Dixon, B. C.; Fischer, R. S. B.; Zhao, H.; O`Neal, C. S.; Clugston, J. R.; Gibb, S. G. (JAMA network Open, 2021)
The COVID-19 pandemic created heightened concern over SARS-CoV-2 transmission during athletic competitions and necessitated innovative mitigation solutions for protecting athletes, staff, and attendees.1,2 During sporting events, efforts like contact tracing pose unique challenges; namely, contact between athletes during play may be brief but recurring, while also challenging to track and triage, especially with interstate competitions.